(untitled) (Archives of Criminology, 1982)
In the present study the young adult drug addicts are discussed who were included in the multidisciplinary research conducted by the Department of Mental Health of the Polish Academy of Sciences. An attempt is made to reveal the psycho-social mechanisms which cause the co-existence of excessive drinking and taking other drugs causing dependence. This problem is insufficiently elucidated both in Polish and foreign scientific literature. We do not cite here the description of the methods employed in the study of sufficient information is provided for in the summary of the study of the progress of dependence and changes in the social behavior of young adult drug addicts, published in the present volume. Attention should be drawn to a difference in the methods: in the present study, we deal first of all with young adult males. Among girls, excessive drinking does not play any important role, therefore the coexistence of alcohol and other drugs in their life stories occurs comparatively rarely. The phenomenon of excessive drinking occurred in 48 boys - drug addicts, which makes 58% of the total of 83 boys. Excessive drinking generally preceded the taking of drugs; alcohol was also used as a mean to soften the abstinence symptoms due to a temporary lack of the basic drug; drinking resulted also from a futile attempt at withdrawal from an advanced morphine habit. The cases of simultaneous drinking and taking of narcotic drugs in order to achieve more intense experiences were rare, as well as those of alternate drinking and taking drugs; in this last case, it meant that the individual was first of all anxious to strenghten the bonds between the members of the group, not yet feeling any mental nor all the more physical symptoms of dependence on alcohol or other drugs. To sum up, we noted in the large part of the addicts the easiness of changing from narcotic drugs to alcohol and vice versa. The possible general interpretation of these facts is as follows: individuals with certain personality deficiencies are characterized by a low tolerance to defeats, stress and tensions, which causes the need to seek the so-called “mental prothesis” or the desire to change one’s own state of mind. These needs and desires can be aggravated by the intensified symptoms of puberty, among them excessive and inadequate emotional reactions, discontent with one’s everyday duties and necessities, states of depression and dysphoria. Both alcohol and narcotic drugs can soothe these needs on temporarily satisfy them, though naturally not identically nor to the same extent. Therefore, where greater efficiency of reaction is desired, the individual may pass on to narcotic drugs. On the other hand, when the person is first of all anxious to soothe the conflicts with his immediate environment, to avoid pressure by the police and the sentence, i.e., meet with more indulgence on the part of his environment and at the same time to have less problems with purchasing a particular drug, and thus to avoid in future the painful withdrawal symptoms - in such cases the conversion from morphine or other drugs to alcohol is probable. Among the individuals who had often drunk alcohol before they started taking narcotic drugs, the later reverse to alcohol to soothe withdrawal symptoms caused by the lack of morphine or other drugs which brought about the state of dependence, is highly probable as the individuals in question already know the influence, of alcohol and the favourable reaction of their organism to it.